Analisis Keterampilan Berpikir Kritis Siswa Madrasah Ibtidaiyah Pada Model Self-Regulated Learning - Muhammad Mushfi El Iq Bali; Tartila Tartila (Hikmah, 2023)
Good learning outcomes are not always in line with students' thinking abilities. Because both are pursued in different ways or separate learning models. This study aims at students' critical thinking skills in the Self-Regulated Learning model of class V Madrasah Ibtidaiyah Miftahul Islam Sukodadi Paiton Probolinggo. The research method used is qualitative, with a case study approach. Data collection techniques using observation, interviews, documentation studies. The subjects in this study were 15 fifth grade students consisting of 6 boys and 9 girls. Research Results: The results of research at Madrasah Ibtidaiyah Miftahul Islam Sukodadi Paiton Probolinggo reveal that: (1) The critical thinking skills of Madrasah Ibtidaiyah students are still developing (2) The Self-Regulated Learning Model has a positive effect on students' critical thinking skills (3) The Self-Regulated Model Learning is more effective or superior to conventional models in the learning stage. Data collection techniques use two main different types, namely tests of critical thinking skills that have been validated and questionnaires. The discussion in this article is very important because it is very useful to make it easier for students to control themselves independently, can also direct their thoughts and actions for predetermined educational goals.